PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Vela, Alda Liga; Yulianto, Fazri; Hakim, Zerri Rahman (Journal of Professional Elementary Education, 2024)
This study aims to explore the potential of the Problem Based Learning (PBL) learning model in improving student learning outcomes and its effectiveness as an alternative learning approach in the modern education era. The type of research used is the method of literature review. The results of the research analyzed were 10 articles that discussed based learning models to improve student learning outcomes. The results of the analysis found that the average results of previous research with the application of the Problem Based Learning (PBL) learning model were proven to be able to improve creative thinking skills, critical thinking, be able to solve problems, be more effective and improve student learning outcomes. It can be concluded that the application of the Problem Based Learning (PBL) Learning Model has great potential to improve student learning outcomes. This research has strong relevance to the development of modern education. This helps improve the quality of learning, prepares students for the complex world of work, provides relevance of subject matter to real life, develops collaborative abilities, and stimulates student creativity